Health education team approach, the panacia of behavioural change against HIV/AIDS and STD’S pandemic for sustainable development (2009)
Sexual Transmitted Disease (STD) are among the major causes of illness in the world especially in the developing countries. Among these STDS are gonorrhea, Non gonococal urethritis, Genital Herpes, Syphilis, Choncroid, Moniliasis trichomomasis and the most deadly is HIV/AIDS. These diseases can lead to organ damage, blindness, deafness, insanity, paralysis and even death. However, these diseases are not just 'a medical problem, they also constitute to social problems with adverse economic consequences. Lock of adequate knowledge is a major factor in the spread of STDS and HIV/AIDS, the knowledge of fact about these diseases is important to their prevention and control. This paper is therefore designed to provide information about healthy safe sexual behaviour to acquaint people with the knowledge of what they can do to reduce the risk of contributing to the spread of and the damage caused by these diseases. It also suggest team approach methods of education that can be taken by all segement of society to create awareness to reduce or prevent the diseases spreading scourge thereby reduce the morbidity and mortality rate for sustainable development of a country, and in the diaspora.